Wujud Al Hilal antara Teori dan Aplikasi - Ahmad Junaidi (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2013)
One of the largest mass organizations in Indonesia is Muhammadiyah. With a very large number of followers, perhaps Muhammadiyah feels the need to make its own decisions regarding the determination of the beginning of the month which will be used as a reference for the implementation of various worship activities. Muhammadiyah believes that Hisa>b with Wuju>d al-Hila>l criteria is a method that provides certainty and convenience in determining the beginning of the hijri>yah month, because the method is based on astronomical mathematical rules that are certain. However, the hope for this methodHowever, the hope for this method has only been achieved at the level of simplifying the system, not at the stage of giving certainty, because certain cases have not been answered using this definitive hisa>b method.